2019
DOI: 10.1111/mcn.12821
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for undernutrition among children 0–59 months of age in Myanmar

Abstract: The prevalence of childhood stunting in Myanmar is one of the highest among the countries of Southeast Asia. Cross‐sectional data from the Myanmar Demographic Health Survey 2015–2016 were used to examine risk factors for stunting, wasting, and underweight among children aged 0–59 months. The prevalence of stunting, wasting, and underweight was 29.0%, 7.3%, and 19.2%, respectively. Accounting for sampling design and weights, multivariable logistic regression was conducted with 35 household, maternal, and child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
7
24
1
5
Order By: Relevance
“…Our study found that children living in rural areas have more prevalence of anthropometric failure compared to urban children. This is consistent with previous studies conducted in Bangladesh [15] and Myanmar [26], and is most likely linked to better living conditions and adequate all years-round food accessibility in urban areas. In addition, our findings show that children from poorer households are more likely to experience anthropometric failure compared with children from richer households.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found that children living in rural areas have more prevalence of anthropometric failure compared to urban children. This is consistent with previous studies conducted in Bangladesh [15] and Myanmar [26], and is most likely linked to better living conditions and adequate all years-round food accessibility in urban areas. In addition, our findings show that children from poorer households are more likely to experience anthropometric failure compared with children from richer households.…”
Section: Discussionsupporting
confidence: 92%
“…This study reveals that children who were born at home have a higher prevalence of anthropometric failure than those born at a health facility. This corresponds with a cross-sectional studies in Tanzania [4] and elsewhere [26]. Health facility delivery is very important because it help to receive appropriate and timely obstetric and medical care, as well as information about childcare to parents.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Several maternal factors have consistently been identified as factors associated with increased risk of wasting in under-five children. Younger maternal age, height below 145 cm, low level of education and low BMI has been linked with increased risk of wasting in several studies [35,41,[58][59][60][61][62][63]. In our analysis, however, only BMI was associated with risk of wasting.…”
Section: Risk Factors For Wastingcontrasting
confidence: 64%
“…Diarrhoea and infections are widely reported to be significantly associated with wasting and underweight among children in various countries [21,29]. In comparison to this study, various studies in different countries proved that younger children are at more risk of wasting compared to older children like in Myanmar [30] and Bangladesh [19,31].…”
Section: Discussionsupporting
confidence: 40%